Marine microalgae on the southern coast of Bahia, Brazil: composition and new records of phytoplankton species - Helen Michelle de Jesus Affe; Lorena Petersen Nascimento Santos; Márcio Ferreira dos Santos; José Marcos de Castro Nunes (Rodriguésia)
Abstract The phytoplankton community is the first link in the aquatic trophic chain and knowledge of its composition is an important tool for ecological characterization; including as potential indicator of anthropic impacts. The southern coast of Bahia is one of the best preserved parts of the Brazilian coast, however, little is known about its biodiversity, especially on marine phycoflora. With the objective of characterizing the composition of microphytoplankton (> 20 µm) in this region, samples were collected by a horizontal dredger using a plankton net (20 µm mesh size) to study the community composition. Water samples were taken from the subsurface using a Van Dorn bottle in order to analyze phytoplanktonic cell concentration. A total of 149 taxa were identified, distributed in the following phyla: Bacillariophyta, Miozoa, Cyanobacteria, Euglenophyta, Haptophyta, and Ochrophyta. Diatoms (63%) and dinoflagellates (26%) were the most representative groups in the specific composition. 43 new taxonomic occurrences were recorded for the coasts of Bahia, Northeastern Brazilian coast, and Brazilian coast.